Pengaruh Pengetahuan Pajak, Tarif Pajak dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak UMKM di Kota Palembang dengan Sosialisasi Perpajakan sebagai Variabel Moderasi - Daniswara Azra Shania Fairuz; Ika Sasti Ferina; Ahmad Raihan Amin (Universitas Muhammadiyah Palembang, 2025)
The purpose of this research to analyze the effect of tax knowledge, tax rates and tax sanctions on the compliance of MSME taxpayers in Palembang City with the tax socialization as a moderating variable. Researchers used the method of determining simple random sampling method in data collection. The sample in this study totaled 100 respondents from MSME individual taxpayers in Palembang City. Palembang. Research data analysis using the Structural Equation Model with the Partial Least Square approach. The results showed that there is an effect of tax rates and tax sanctions on taxpayer compliance of MSMEs. UMKM. Other results show that there is no effect of tax knowledge on compliance of MSME taxpayers. Tax socialization cannot moderate the effect of tax knowledge, tax rates and tax sanctions on MSME taxpayer compliance.